2014
DOI: 10.17221/7241-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neospora caninum on reproductive performance and the efficacy of treatment with a combination of sulphadiazine-trimethoprim and toltrazuril: a longitudinal field study

Abstract: ABSTRACT:This study was designed to determine the prevalence of Neospora caninum, the effect of infection on abortion and fertility parameters and the efficacy and outcomes with combination treatment in a dairy farm with high abortion rates and low fertility parameters. Four hundred and eighty-six cows were tested using the immunofluorescence antibody test (IFAT). The seroprevalence of N. caninum was 19%. Sulphadiazine-trimethoprim and toltrazuril were administered to the seropositive animals. The risk of abor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
(70 reference statements)
3
1
0
Order By: Relevance
“…Antibody responses to N. caninum had unfavorable genetic associations with fertility traits in the present study, which is similar to reported phenotypic associations (Hall et al, 2005;Canatan et al, 2014). In a study of 486 Turkish dairy cows, Canatan et al (2014) reported cows positive for the antibody response to N. caninum required almost twice the number of inseminations and had, on average, a 77 d longer calving to conception interval compared to cows negative for the antibody response to the N. caninum. The increased odds of an abortion in N. caninum infected animals was 3.5 (the median value from a review of 10 studies) in dairy cows (Reichel et al, 2013).…”
Section: Genetic Correlations With Fertility Traitssupporting
confidence: 87%
“…Antibody responses to N. caninum had unfavorable genetic associations with fertility traits in the present study, which is similar to reported phenotypic associations (Hall et al, 2005;Canatan et al, 2014). In a study of 486 Turkish dairy cows, Canatan et al (2014) reported cows positive for the antibody response to N. caninum required almost twice the number of inseminations and had, on average, a 77 d longer calving to conception interval compared to cows negative for the antibody response to the N. caninum. The increased odds of an abortion in N. caninum infected animals was 3.5 (the median value from a review of 10 studies) in dairy cows (Reichel et al, 2013).…”
Section: Genetic Correlations With Fertility Traitssupporting
confidence: 87%
“…These results agree with some previous reports that also demonstrated an adverse effect of N. caninum on reproductive efficiency in dairy herds [38]. In particular, the number of inseminations for conception was higher in seropositive animals than in seronegative ones [7,8,39,40]. Although a few studies did not observe any influence of N. caninum infection in early pregnancy [33,41], it was suggested that an increase in the number of services necessary for cows to conceive may indicate embryonic death followed by fetal reabsorption, leading to a return to heat [9,42].…”
Section: Discussionsupporting
confidence: 92%
“…Although a few studies did not observe any influence of N. caninum infection in early pregnancy [33,41], it was suggested that an increase in the number of services necessary for cows to conceive may indicate embryonic death followed by fetal reabsorption, leading to a return to heat [9,42]. Moreover, some studies also reported an increased calving to conception interval in seropositive cows [9,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the increased seroprevalence found in cows with repeated breeding syndrome supports the results of previous research conducted in Turkey (Canatan et al, 2014), Greece (Lefkaditis et al, 2020), and Italy (Villa et al, 2022), which demonstrated the adverse effects of N. caninum infection on the reproductive capacity of animals. According to the studies cited, the number of inseminations per conception was higher among seropositive animals compared to seronegative animals.…”
Section: Resultssupporting
confidence: 87%